The Influence of Brand Image and Product Quality on Customer Loyalty of Kopi Kenangan and Fore Coffee in Indonesia - Terry Sandrina (Green Publisher Indonesia, 2026)
The rapid growth of the Indonesian coffee industry has intensified competition among local brands, making product innovation and brand differentiation essential for maintaining customer interest. This study investigates how customer loyalty is influenced by brand image and product quality, with customer satisfaction acting as a mediating variable, and compares these relationships between the two brands. Using a quantitative explanatory approach and Partial Least Squares–Structural Equation Modeling (PLS-SEM), data were collected from 312 respondents aged 18–40 who had purchased from either brand in the past three months. All constructs—Brand Image, Product Quality, Customer Satisfaction, and Customer Loyalty—were measured reflectively using a five-point Likert scale and analyzed with SmartPLS 4, including mediation testing and Multi-Group Analysis (MGA). The results show that Brand Image and Product Quality significantly and positively affect Customer Satisfaction and Customer Loyalty, while Customer Satisfaction strongly influences Customer Loyalty, confirming its mediating role in line with Expectation-Confirmation Theory (Oliver) and the Customer-Based Brand Equity Model. MGA findings reveal brand-specific patterns: Kopi Kenangan’s loyalty is more strongly driven by Brand Image, emphasizing emotional connection, accessibility, and brand engagement, whereas Fore Coffee’s loyalty is more influenced by Product Quality, reflecting its focus on consistency, sensory experience, and product excellence. Overall, the study confirms that brand image and product quality significantly shape loyalty through satisfaction, with varying strengths across brands, offering practical insights for companies seeking sustainable competitive advantage in Indonesia’s modern coffee market.